Az atomerőmű-bővítés térségfejlesztésre gyakorolt hatása - Sipos, Tamás (Közép-Európai Közlemények, 2012)
The planned expansion of the Paks Nuclear Power Plant has a significant relevance not only in the context of Paks city but in the development of the whole Southern-Danube region as well. Such a great investment creates opportunity for the small and the medium size enterprises to stabilize their position and to ensure the subsistence of their employees. Furthermore the expansion generates broader and comprehensive effects regionally because Paks – due to its geographical location – potentially osculates 3 regions where the investment can more directly evolve its effects. The project also has a decisive role in the perspective of Sustainable Development – the satisfaction of the needs of the present generations should not limit the future generations in the satisfaction of their own needs – due to the fact that the society has an ever growing hunger for energy this investment might able to ease this need at least for a while. To consider the national and international electricity industry’s development and to decrease Hungary’s import dependencies in 2009 the Hungarian parliament had decided to give its theoretical approval for the preparation of the implementation of the new units at Paks.